2021
DOI: 10.3390/biomedicines9111579
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins and Cardiovascular Disease: An Update on the Clinical Significance of Atherogenic Small, Dense LDL and New Therapeutical Options

Abstract: Dyslipidemia is a potent risk factor for the genesis and progression of cardiovascular disease (CVD), and both the concentration and type of low-density lipoproteins (LDL) augment this association. The small, dense LDL (sdLDL) subfraction is the subtype which is most strongly predictive of atherosclerosis and cardiovascular events. In addition to the traditionally available lipid-lowering treatment options, certain novel therapies have been shown to favorably impact sdLDL, among them the antidiabetic class of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
2
16
0
Order By: Relevance
“…Hypercholesterolemia, hypertriglyceridemia, elevated LDL-C levels, and diminished LDL-C are known cardiovascular disease (CVD) risk factors among the human population. Similarly, compelling experimental data from animal studies have implicated high serum total cholesterol (TC) concentration, high LDL-C, and low HDL-C as major risk factors in the onset of CVD (Noh et al, 2022;Rizvi, et al, 2021). Additionally, studies have shown a strong positive association between elevated TC to HDL-C ratio (TC/HDL-C) and pathogenesis of left ventricular hypertrophy, ischemic stroke, and coronary heart disease (CHD) (Zhang, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Hypercholesterolemia, hypertriglyceridemia, elevated LDL-C levels, and diminished LDL-C are known cardiovascular disease (CVD) risk factors among the human population. Similarly, compelling experimental data from animal studies have implicated high serum total cholesterol (TC) concentration, high LDL-C, and low HDL-C as major risk factors in the onset of CVD (Noh et al, 2022;Rizvi, et al, 2021). Additionally, studies have shown a strong positive association between elevated TC to HDL-C ratio (TC/HDL-C) and pathogenesis of left ventricular hypertrophy, ischemic stroke, and coronary heart disease (CHD) (Zhang, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This beneficial action is expected to be supported with additional beneficial effects on improvements in lipid profiles, mainly through reduction of the atherogenic small dense LDL subclasses, which have a specific physico-chemical composition and metabolic properties, including a reduced affinity for the LDL receptor, lower antioxidant capabilities and higher susceptibility to oxidation [32]. Small dense LDLs have greater arterial entry and retention abilities, and their oxidation in the intima is considered to represent the very first step of the atherosclerotic cascade [33]. Additionally, HbA1c improvement as well as reduction in hsCRP will be studied.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, n-3 PUFAs suppress the generation of small dense LDL by reducing the expression of cholesterol ester transfer protein (CETP) which shuttles cholesteryl ester from HDL to apo-B protein [ 117 ]. Thus, n-3 PUFAs have various improving effects on lipid profile, and as a result, exert a strong anti-arteriosclerotic effect in combination [ 118 , 119 ].…”
Section: N-3 Pufas Protect the Heartmentioning
confidence: 99%